2000
DOI: 10.3233/icg-2000-23103
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Constrained Optimisation

Abstract: The latest 6-man chess endgame results confirm that there are many deep forced mates beyond the 50-move rule. Players with potential wins near this limit naturally want to avoid a claim for a draw: optimal play to current metrics does not guarantee feasible wins or maximise the chances of winning against fallible opposition. A new metric and further strategies are defined which support players' aspirations and improve their prospects of securing wins in the context of a k-move rule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…As conjectured by Haworth (2000), KQPKQ and KBBKNN provide positions where ali combinations of SC, SM-and SZ" fail to safeguard a win available under the 50-move rule: the examples here were found by Bourzutschky (2003). Similar positions for other endgames were found by Tamplin (2003).…”
Section: Endgame Strategiesmentioning
confidence: 54%
See 2 more Smart Citations
“…As conjectured by Haworth (2000), KQPKQ and KBBKNN provide positions where ali combinations of SC, SM-and SZ" fail to safeguard a win available under the 50-move rule: the examples here were found by Bourzutschky (2003). Similar positions for other endgames were found by Tamplin (2003).…”
Section: Endgame Strategiesmentioning
confidence: 54%
“…DTM data is of interest in itself, even if conversion, i.e., change of force, is usually adopted as an interim objective in human play. However, more effective endgame strategies using different metrics can be adopted, particularly by computers (Haworth, 2000. A further practica!…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with all extant EGTs, castling is assumed not to be an option, currently reasonable as castling rights have never survived to move 49 [43], but this does mean that EGTs will not help solve some Chess Studies. 15 There are arguments for computing EGTs to a variety of metrics [45] and therefore they need to identify their particular metric to any chess-engine using them. It can be demonstrated that when a chess-engine mistakes a DTZ EGT for a DTM EGT, it will prefer the position-depth in the current phase of play before a capture to that in the next phase, resulting in the bizarre refusal of a piece en prise.…”
Section: Phase 3: Usementioning
confidence: 99%
“…In a drawn position, how best can the attacker pressure the defender or the defender resist the attacker (Levy 1987(Levy , 1991Nunn, 2002;Schaeffer 1991Schaeffer , 1997? How can the opponent be given the best opportunity to concede depth in a situation where a draw claim is possible (Haworth, 2000(Haworth, , 2001? How can a player identify and adapt to apparent opponent fallibility?…”
Section: Introductionmentioning
confidence: 99%